Slovenija VII - Kladnik, Drago (Vodniki LGD, 2017)
The 7th guidebook contains six excursions of the Ljubljana Geographical Society which took place between September 2012 and November 2014. An additional excursion of the Geomorphological Association of Slovenia from March 2012 was added. Every excursion is thematically unique, thus mutually complementing all of them to different collage and displaying the broad geographical horizon.The first excursion guides us to the plateau of Banjšice and to Čepovanski dol, the second introduces us with different landscape, historical and artistic elements of the valley of Selška Sora, the third takes us to the east of the country to Obsotelje and Kozjansko, the fourth deals with the valley of Dravinja River and the learning polygons, the fifth deals in details with Goričko~the least developed Slovenian region, the sixth takes us through the history of arms in the Park of the military history in Pivka, the last exursion gives us detailed introduction with the less known karstic features on flysch and the measurement of the erosion in flyschy Slovene Grey Istria.